2016
DOI: 10.18805/ijar.v0i0f.3786
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of orf virus (ORFV) isolation in continuous lamb testis cells (OA3.Ts) and development of a co-culture method with infected cells to increase infectivity

Abstract: Continuous foetal lamb testis cells OA3.Ts was used to compare the isolation of a vaccine orf virus (ORFV) strain that had been adapted to primary lamb testes cells, with scab derived wild-type/field ORFV isolates. The wild type virus showed an accelerated and exaggerated cyto-pathic effect (CPE) than the vaccine virus as has been demonstrated by immunofluorescent detection of viral antigen using ORFV monoclonal antibodies. ORFV could be successfully isolated in OA3.Ts foetal lamb testes cells and can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Besides the current applications, other confirmatory applications were also employed. In our earlier studies, ORFV has also been successfully cultured in continuous lamb testis cells (OA3.Ts) (Nashiruddullah et al, 2016) and the virus has been demonstrated by immunofluorescence and visualized by Transmission Electron Microscopy (TEM) (Nashiruddullah et al, 2018). ELISA applications for antibody detection showed positive results and were consistent.…”
Section: Dot-elisa For Antibody Detectionmentioning
confidence: 88%
See 1 more Smart Citation
“…Besides the current applications, other confirmatory applications were also employed. In our earlier studies, ORFV has also been successfully cultured in continuous lamb testis cells (OA3.Ts) (Nashiruddullah et al, 2016) and the virus has been demonstrated by immunofluorescence and visualized by Transmission Electron Microscopy (TEM) (Nashiruddullah et al, 2018). ELISA applications for antibody detection showed positive results and were consistent.…”
Section: Dot-elisa For Antibody Detectionmentioning
confidence: 88%
“…Live attenuated vaccine virus (OrfMuk 59/05, batch 06/ 09) isolated from goat and previously propagated in primary lamb testis cells (PLT) produced at poxvirus disease laboratory, Division of Virology, Mukteshwar were used as a reference ORFV strain. Tissue lysates from scab samples were prepared according to Nashiruddullah et al (2016).…”
Section: Orfvirus (Orfv) Antigen Detectionmentioning
confidence: 99%
“…Formation of CPE due to virus growth was observed. TCID 50 values of the produced virus were determined by the Spermen-Kaerber method (Ergin and Köklü 1974;Nashirudddullah et al 2016).…”
Section: Detection Of Infective Titer Of Pathogen Ce Virusmentioning
confidence: 99%
“…At the end of the incubation period, 50 µl of MDBK cell culture was added to all wells and incubated in 5% CO 2 medium for 10 days at 37°C. Cells were checked daily for CPE formation (Nashirudddullah et al 2016).…”
Section: Serum Neutralization Test (Snt)mentioning
confidence: 99%
“…CPE formation due to virus multiplication was observed. The titer of CE vaccine virus were determined according to the Spermen-Kaerber method (Ergin and Köklü 1974;Burleson et al 1992;Nashirudddullah et al 2016).…”
Section: Collection Of Ce Final Product (E (P) Ck 17 -Mdbk 5 )mentioning
confidence: 99%